2021
DOI: 10.1002/jemt.23935
|View full text |Cite
|
Sign up to set email alerts
|

Marginal gaps and voids of three root‐end filling materials: A microcomputed tomographic study

Abstract: A root‐end filling material is required to fill the root‐end cavity without gaps or voids, to prevent root canal reinfection and to provide periapical healing. Thus, this study evaluated the volume of marginal gaps and voids of three root‐end filling materials using microcomputed tomography (micro‐CT). Thirty maxillary incisors were prepared and filled with gutta‐percha and endodontic sealer. The specimens were scanned using micro‐CT and distributed into three groups (n = 10): White MTA, MTA Repair HP, and Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
(53 reference statements)
1
1
0
Order By: Relevance
“…Confirming the results obtained in the cell viability assays (MTS and LIVE/DEAD), the materials show similar results to the life control group, with the number of cells with fluorescent green-stained nuclei being lower in the Bio-C® Sealer group in comparison with MTA Repair HP®. These results agree with the data found in the scientific literature, where they conclude that, in addition to Bio-C® Sealer and MTA Repair HP® being the most studied silicate-based sealants from 2005 to 2020 (28,29), only a few studies showed slight genotoxicity in mammalian cells. Dos Santos et al report that MTA Angelus is the most tested sealant and showed an absence of genotoxicity with the comet assayin L5178Y cells, CHO-K1 cells, hPB lymphocytes, and 3T3-L1 cells; likewise, this sealant does not show genotoxicity evaluated with the micronucleus test performed on V79 cells and bone marrow cells from swiss mice (30).…”
Section: Discussionsupporting
confidence: 91%
“…Confirming the results obtained in the cell viability assays (MTS and LIVE/DEAD), the materials show similar results to the life control group, with the number of cells with fluorescent green-stained nuclei being lower in the Bio-C® Sealer group in comparison with MTA Repair HP®. These results agree with the data found in the scientific literature, where they conclude that, in addition to Bio-C® Sealer and MTA Repair HP® being the most studied silicate-based sealants from 2005 to 2020 (28,29), only a few studies showed slight genotoxicity in mammalian cells. Dos Santos et al report that MTA Angelus is the most tested sealant and showed an absence of genotoxicity with the comet assayin L5178Y cells, CHO-K1 cells, hPB lymphocytes, and 3T3-L1 cells; likewise, this sealant does not show genotoxicity evaluated with the micronucleus test performed on V79 cells and bone marrow cells from swiss mice (30).…”
Section: Discussionsupporting
confidence: 91%
“…BCR has greater filling capacity and less volumetric change than MTA Repair HP 15 , in addition it has adequate radiopacity 14 , less porosity and gaps in the material/dentin interface 16 . However, BCR has shown a higher percentage of voids when compared with White MTA (Angelus, PR, Brazil) 17 . However, there are no reports in the literature regarding the interaction of this material with dentin after immersion in different solutions.…”
Section: Introductionmentioning
confidence: 98%
“…Calcium silicate cement materials, colloquially denoted as “Bioceramic”, in both forms, sealer [ 8 ] or thicker mixture [ 9 ], are considered as the ideal endodontic material for retrograde treatment due to their excellent physicochemical and biological properties [ 10 , 11 , 12 , 13 , 14 , 15 ], including biocompatibility and stability. These inorganic and non-corrosive ceramic cements contain tricalciums silicate and various radiopaque powders [ 16 ].…”
Section: Introductionmentioning
confidence: 99%